The Influence of Independence, Objectivity, Proficiency and Professional Accuracy of Internal Auditors on Fraud Prevention in X Hospital - Wedi Rusmawan Kusumah; Tony Pranoto (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient and emergency services. In carrying out hospital operations, it is possible for fraud to occur. This study aims to determine whether the independence, objectivity, skills, and professional accuracy of the internal auditors affect the prevention of fraud in X Hospital. This research uses a population with a total of 54 respondents. The type of data used in this study is quantitative data using primary data sources derived from questionnaires distributed to employees at X Hospital and then processed using SPSS. The results of the study show that (1) the independence of the internal auditors has a significant effect on fraud prevention, (2) the objectivity of the internal auditors has a significant effect on fraud prevention, (3) the competence of the internal auditors has a significant effect on fraud prevention and (4) the professional accuracy of the internal auditors has a significant effect on fraud prevention.